Filsafat Sosial; Pribumisasi Ilmu-Ilmu Sosial - Firdaus M. Yunus (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
Social philosophy is a branch of philosophy which studies social issues in a critical, radical and comprehensive manner. Since it was formulated, Social philosophy has deconstructed the public understanding in term of not all the creations under the sky directly regulated by the power of God forever and ever. Demolition of public understanding on a large scale occurred just as the emergence of the French revolution, which undermined the feudal social order and begin the process of democratization that generated the spectacular surprises, since no one had previously imagined that a social order which was supposed unchangeable and forever blessed by the will of God has been overhauled and replaced by thoughts of human being. This situation has been strengthen by the development of Frankfurt’s school which developed a critical social science which gradually has been spread to all over the world.